Outbreak of waterborne hepatitis E in Hyderabad, India, 2005 - SAILAJA, B.; MURHEKAR, M. V.; HUTIN, Y. J.; KURUVA, S.; MURTHY, S. P.; REDDY, K. S. JOWAHER; RAO, G. MASTAN; GUPTE, M. D. (Epidemiology and infection, 2009)
A large outbreak of hepatitis E occurred in 2005 in Hyderabad, Andhra Pradesh, India. A total of 1611 cases were reported between 1 March and 31 December 2005 (attack rate 40/100 000). The epidemic curve suggested a continuing common source outbreak. Cases were centred around open sewage drains that crossed the old city. The attack rate was significantly higher in neighbourhood blocks supplied by water supply lines that crossed open drains (203/100 000) than in blocks supplied by non-crossing water pipes with a linear trend (38/100 000, P<0·00001). Crossing water pipelines were repaired and the attack rates declined.